Use of Postpartum Care: Predictors and Barriers - Jessica N. DiBari; Stella M. Yu; Shin M. Chao; Michael C. Lu (Hindawi Limited, 2014)
This study aimed to identify actual and perceived barriers to postpartum care among a probability sample of women who gave birth in Los Angeles County, California in 2007. Survey data from the 2007 Los Angeles Mommy and Baby (LAMB) study (N = 4,075) were used to identify predictors and barriers to postpartum care use. The LAMB study was a cross-sectional, population-based study that examined maternal and child health outcomes during the preconception, prenatal, and postpartum periods. Multivariable analyses identified low income, being separated/divorced and never married, trying hard to get pregnant or trying to prevent pregnancy, Medi-Cal insurance holders, and lack of prenatal care to be risk factors of postpartum care nonuse, while Hispanic ethnicity was protective. The most commonly reported barriers to postpartum care use were feeling fine, being too busy with the baby, having other things going on, and a lack of need. Findings from this study can inform the development of interventions targeting subgroups at risk for not obtaining postpartum care. Community education and improved access to care can further increase the acceptability of postpartum visits and contribute to improvements in women's health. Postpartum care can serve as a gateway to engage underserved populations in the continuum of women's health care.